FAKTOR YANG BERHUBUNGAN DENGAN PEMANFAATAN PELAYANAN KESEHATAN PASIEN DI PUSKESMAS LEPO-LEPO KOTA KENDARI TAHUN 2020 - Hinarti Hinarti; Nani Yuniar; Yasnani Yasnani (Jurnal Administrasi Kebijakan Kesehatan Universitas Halu Oleo, 2020)
Abstrak Latar Belakang: Kesehatan merupakan suatu keadaan sehat yang utuh baik secara fisik, mental dan sosial serta bukan hanya keadaan bebas dari penyakit atau kecacatan yang memungkinkan setiap orang dapat hidup produktif secara sosial dan ekonomi. Pelayanan kesehatan adalah setiap upaya yang diselenggarakan sendiri atau bersama-sama dalam suatu organisasi untuk memelihara dan meningkatkan kesehatan mencegah dan menyembuhkan penyakit serta memulihkan kesehatan perorangan, keluarga, kelompok dan  masyarakat.Tujuan: Tujuan penelitian ini adalah untuk mengetahui faktor yang berhubungan dengan pemanfaatan pelayanan kesehatan pasien di Puskesmas Lepo-Lepo Kota Kendari.Metode: Metode penelitian yang digunakan adalah observasional analitik dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah  pasien yang berkunjung di Puskesmas Lepo-Lepo Kota Kendari yaitu sebanyak 401 pasien. Sampel penelitian ini yaitu 200 responden di Puskesmas Lepo-Lepo Kota Kendari. AbstractBackground: Health is a state of health that is intact both physically, mentally andsocially and not just a state free from disease or disability that allows everyone to live productively socially and economically. Health services are any efforts carried out alone or together in an organization to maintain and improve health to prevent and cure illnesses and restore the health of individuals, families, groups and communities.Objectives:  The purpose of this study was to determine the factors associated with the utilization of patient health services at the Lepo-Lepo Health Center in Kendari City.Methods: The research method used was observational analytic with cross sectional approach. The population in this study were patients who visited the Lepo-Lepo Health Center in Kendari City as many as 401 patients. The sample of this research is 200 respondents in the Lepo-Lepo Health Center in Kendari City.Results: Asalisis used was tes showed that there is relationship between community trust about patiens wit the use of paints and the use of patients health (pvalue: 0,08)., there is a relationship between husband support about patiens and the use of patients health (pvalue: 0,02)., there is relationship between the availability of health facilities about patiens with the utilization of patient health s (pvalue: 0,00)., there is no relationship between complaint of ilness about patients with utilization patiens health (pvalue: 0,00).